High School Female Students\' Overweight Toward Emotional Intelligence - Jafar Shabani; Najmh Sargolzaie (Shahid Sadoughi University of Medical Sciences, 2021)
Introduction: The prevalence of overweight and obesity is increasing at an alarming rate. They both have two-way communication with onechr('39')s emotional stresses and psychological distresses. Methods: This research is a descriptive-correlation study. The sample size included 370 female high school students in Gonbad, Galikesh, Azadshahr, and Kalaleh, in the east of Golestan province (Iran) in 2018. To select the participants, 370 students with a body mass index (BMI) between 25 and 29.9 kg/m² were selected as samples, and the Emotional Intelligence (EQ) questionnaire was handed out Pearsonchr('39')s correlation and regression analyses were also employed in this study (p<0.05). Results: The results demonstrated that there is a direct, yet inverse relationship between students' total EQ (r= -0.465, p =0.01), intrapersonal (r= -0.421,p= 0.01), interpersonal (r= -0.325, p= 0.01), adaptability (r= -0.391, p= 0.01), stress management (r= -0.401, p= 0.01), general mood (r= -0.383, p= 0.01), and their overweight. Also the Regression Analysis findings show that the EQ sub-scales are significant predictors for overweight R2 = 0.431, F = 39.457, and (p= 0.00). It suggests that the higher the EQ and its subscales scores among the students increase, the less weight they own, and vice versa. Conclusion: The findings of this study will enhance social public awareness of the side- effects of overweight, equipping the public with some counseling to lose weight through using EQ for students suffering overweight.